Cognitive-complexity and coping style: the impact of cognitive complexity on attributional style and coping behaviors - Dempsey, David John, author; Rosén, Lee, advisor; Boyer, William N., committee member; Fritz, Janet J., committee member; Chavez, Ernest L., committee member (Colorado State University. Libraries, 2002)
Cognitive-complexity is an individual difference variable that measures the degree of multidimensionality and differentiation of the self-concept. Greater cognitive-complexity is presumed to moderate the impact of events because the relatively greater number of distinct self-aspects serves to confine spill over of thoughts and feelings associated with an event to only those immediately relevant self-aspects, leaving remaining self-aspects unaffected. Cognitive-complexity has demonstrated significant stress-buffering effects in studies of stress and health outcomes. The purpose of the present study is to examine the possible cognitive and behavioral mechanisms through which greater cognitive-complexity may protect from the deleterious effects of stress. The study utilizes questionnaire data to examine the impact of cognitive-complexity, four personality stress-moderators, and gender on coping decisions and attributions for negative outcomes. While greater cognitive-complexity was associated with more frequent use of active-cognitive coping, it failed to make a significant contribution to the prediction of either active-behavioral or avoidance coping categories or to any of the attribution dimensions. The lack of findings in these studies suggests that further research is needed to determine whether the present measure of cognitive-complexity is reliable and valid and secondly, if it is the variable for predicting cognitive and affective reactions to events.
Keywords: psychotherapy; clinical psychology